A modalidade facultativa no português falado no Ceará: uma análise baseada na gramática discursivo-funcional - Lima, Liliane Viana (2018)
The objective of this paper is to investigate the manifestation of the facultative modality in Brazilian Portuguese spoken in Ceará in view of the levels and layers of the Discursive-Functional Grammar, in order to show the role of the Contextual and Grammatical Components for the expression of the category. According to GDF and based on the idea that the optional modality is linked to the notions of physical / circumstantial conditions, abilities and capacities (HENGEVELD; MACKENZIE, 2008), we assume that the Contextual Component interacts with the Grammatical Component bringing relevant information for the manifestation of the optional modality. We used a sample of the PROFALA corpus, referring to the speech of Ceará, composed of 60 DID interviews in order to analyze how the facultative modality manifests itself in the Portuguese spoken in Ceará. Our qualitative and quantitative description was as follows: a) reading the interviews for the identification of the facultative modalizers; b) analysis of the incidence of the facultative modality; c) quantitative treatment of occurrences with SPSS statistical analysis software, in order to codify and quantify the cases found; d) interpretation of quantitative results in the light of functionalist theoretical principles, more specifically GDF. After crossing the results obtained, we verified the existence of significant relations: (i) as for the components of the Context Component, we saw that the 'sex' category was the most statistically significant, maintaining relations with 'reality conditions',' word classes 'and' tense '; (ii) regarding the Interpersonal Level, we discuss about the [+ inclusive] parameter, the most used by the speakers; (iii) At the Representational Level, we saw the predilection for the facultative modality oriented to the participant, especially regarding the 'acquired' subtype, besides the expressive use of negative polarity; (iv) Regarding the Morphosyntactic Level, the results showed that the optional modality in Portuguese spoken in Ceará is expressed primarily by means of 'words', especially by the verb 'poder'. Therefore, with the discussion of the final results found, we hope to contribute with the description and analysis of the facultative modality in Portuguese spoken in Ceará.